The effectiveness of borneol on pharmacokinetics changes of four ginsenosides in Shexiang Baoxin Pill in vivo. (7th October 2013) - Jiang, Peng; Fu, Peng; Xiang, Li; Wang, Shuping; Liu, Xiaojun; Yang, Ling; Tao, Jianfei; Chen, Zhongliang; Zhan, Changsen; Huang, Ximing; Liu, Runhui; Zhang, Weidong
ABSTRACT Shexiang Baoxin Pill (SBP) is a traditional Chinese medicine, widely used for cardiovascular diseases in the clinic. Ginsenosides are important effective components in SBP, but their pharmacokinetic characteristics are still not known. In this paper, we studied the pharmacokinetics of ginsenoside Rb1, Rc, Re and Rg1 in SBP and investigated the effect of borneol on the pharmacokinetic characteristic of ginsenosides based on an Agilent G6410A triple quadrupole LC/MS system. Results showed that the pharmacokinetic parameters of ginsenoside Rb1, Rc, Re and Rg1 in rat plasma after oral administration of SBP are significantly different with oral administration of SBP without Borneolum Syntheticum. Plasma pharmacokinetic profiles after oral administration of ginsenoside Rb1, Rc, Re, Rg1 and co‐administration with borneol at three different ratios (10:1, 1:1 and 1:10 ginsenoside vs borneol, w/w) were also determined. It was demonstrated that borneol can elevate the plasma concentration of ginsenosides after co‐admininstration. Copyright © 2013 John Wiley & Sons, Ltd.